2016
DOI: 10.1007/s11695-016-2325-7
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Outcomes of Vagal Nerve Blocking (vBloc) for the Treatment of Obesity in the ReCharge Trial

Abstract: BackgroundThe ReCharge Trial demonstrated that a vagal blocking device (vBloc) is a safe and effective treatment for moderate to severe obesity. This report summarizes 24-month outcomes.MethodsParticipants with body mass index (BMI) 40 to 45 kg/m2, or 35 to 40 kg/m2 with at least one comorbid condition were randomized to either vBloc therapy or sham intervention for 12 months. After 12 months, participants randomized to vBloc continued open-label vBloc therapy and are the focus of this report. Weight loss, adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
103
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(105 citation statements)
references
References 15 publications
1
103
1
Order By: Relevance
“…Gastric electrical stimulation is used to help patients with delayed stomach-emptying of solid foods (gastroparesis), which is commonly observed in patients with diabetes (Abell et al 2003). Vagal nerve block (vBloc) therapy was recently approved by the FDA for certain patients with morbid obesity (Apovian et al 2017). Clinical trials on vBloc therapy reported improvements in blood glucose control for patients with obesity and type 2 diabetes but were not sustained after 24 months (Herrera et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Gastric electrical stimulation is used to help patients with delayed stomach-emptying of solid foods (gastroparesis), which is commonly observed in patients with diabetes (Abell et al 2003). Vagal nerve block (vBloc) therapy was recently approved by the FDA for certain patients with morbid obesity (Apovian et al 2017). Clinical trials on vBloc therapy reported improvements in blood glucose control for patients with obesity and type 2 diabetes but were not sustained after 24 months (Herrera et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The block of nerve conduction by kHz HFBS has been approved by FDA for human application to treat obesity or amputation limb pain . Therefore, HFBS block of the pudendal nerve is expected to be safe for restoring bladder function after SCI because it will only be used for a short period during voiding that only occurs five to eight times per day for 2 to 5 minutes each time.…”
Section: Discussionmentioning
confidence: 99%
“…Gastric stimulation was associated with decrease caloric intake and gastric accommodation, but weight loss was not measured in this study because a temporary pacing device was used [42]. Of note, there is a surgically placed device of this kind in use (vBloc, EnteroMedics, St. Paul, MN, USA), which has shown 21% EWL (8% total weight loss) after 2 years [43]. …”
Section: Endoscopic Bariatric Techniquesmentioning
confidence: 99%